1999
DOI: 10.1126/science.283.5399.190
|View full text |Cite
|
Sign up to set email alerts
|

Paleolithic Population Growth Pulses Evidenced by Small Animal Exploitation

Abstract: Variations in small game hunting along the northern and eastern rims of the Mediterranean Sea and results from predator-prey simulation modeling indicate that human population densities increased abruptly during the late Middle Paleolithic and again during the Upper and Epi-Paleolithic periods. The demographic pulses are evidenced by increasing reliance on agile, fast-reproducing partridges, hares, and rabbits at the expense of slow-reproducing but easily caught tortoises and marine shellfish and, concurrently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
241
0
5

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 495 publications
(253 citation statements)
references
References 13 publications
(2 reference statements)
7
241
0
5
Order By: Relevance
“…Several decades of research, primarily on faunal remains, has shown that foragers were indeed casting their nets wider, starting perhaps 50,000 years ago. This research has also shown not only that the new animal foods were taxonomically more diverse than in earlier periods but also that they were more costly in terms of effort to procure (4)(5)(6)46). Whether plant foods went along on this broad-spectrum ride has never been demonstrated for lack of archaeobotanical data.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Several decades of research, primarily on faunal remains, has shown that foragers were indeed casting their nets wider, starting perhaps 50,000 years ago. This research has also shown not only that the new animal foods were taxonomically more diverse than in earlier periods but also that they were more costly in terms of effort to procure (4)(5)(6)46). Whether plant foods went along on this broad-spectrum ride has never been demonstrated for lack of archaeobotanical data.…”
Section: Discussionmentioning
confidence: 83%
“…Since Flannery proposed the ''broad spectrum revolution'' (BSR), researchers have found support for the hypothesis in faunal assemblages from sites across the Mediterranean basin dating back as early as 50,000 years ago (3)(4)(5). Among them are Stiner and colleagues (4)(5)(6), who went a step further and refined the BSR hypothesis by looking at dietary breadth in terms of ''cost͞benefits'' rather than taxonomic species diversity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that with the technologies the Neanderthals had in hand, certain plant foods would have been more highly-ranked than small, fast, and hard-to-catch animals (Stiner and Kuhn, 1992;Stiner et al, 1999Stiner et al, , 2000 because the plants were accessible without the development and curation of new tools (Bright et al, 2002;Bird and O'Connell, 2006). At low population densities, large mammals and a broad plant diet probably would have been sufficient to meet the dietary needs of Neanderthals (O'Connell, 2006;Hockett, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It seems that these animals were caught only if the occasion arose (cf. Faith 2011;Stiner et al 1999); the same pertained to large and dangerous animals (Faith 2008). With its body size larger than that of the kobus, the buffalo is a dangerous animal, hence the choice of the former as the Bfirst rankŝ pecies seems to be fully rational.…”
Section: Hunting and Fishing Strategiesmentioning
confidence: 99%